Child disability and maternal work participation: New evidence from India - Prachi Gupta; Upasak Das; Ashish Singh (Kiel Institute for the World Economy (IfW), 2013)
Using data from the India Human Development Survey, this paper analyses the relationship between child disability and maternal work participation for India. The authors' findings suggest a significant positive relationship between child disability and the work participation of the urban mothers who are wives of household heads. These mothers are 1.27 times as likely to participate in labour market as mothers (wives in urban areas) without a disabled child. However, for the same mothers, child disability significantly affects the weekly work hours of those participating in the labour market in a negative manner with presence of a disabled child reducing the weekly work hours by 3.6 hours. For the rural mothers and the mothers in urban areas who are household heads, our findings do not suggest any significant association between child disabilities and their work participation (or weekly work hours).
Keywords: J10; J22; 330; Child disability; maternal work participation; India